-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathHW6.tex
169 lines (145 loc) · 6.94 KB
/
HW6.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
\documentclass[12pt]{article}
\usepackage{amssymb,amsmath,graphicx,mathtools}
\usepackage{listings}
\usepackage[margin=0.75in]{geometry}
\parindent 16 pt
\usepackage{fancyhdr}
\pagestyle{fancy}
\fancyhead[R]{Swupnil Sahai}
\fancyhead[L]{Stat G6108 HW 6}
\DeclarePairedDelimiter\ceil{\lceil}{\rceil}
\DeclarePairedDelimiter\floor{\lfloor}{\rfloor}
\begin{document}
% CUSTOM SHORTCUTS
\def\ci{\perp\!\!\!\perp}
\def\ex{\mathbb{E}}
\def\prob{\mathbb{P}}
\def\ind{\mathbb{I}}
\def\grad{\triangledown}
\def\bigo{\mathcal{O}}
% PROBLEM 1
\noindent
(1) Firstly, we know from Inference I that the join distribution of the order statistics is $n!$. Additionally, we know that for every $t>0$, if the number of arrivals in the time interval $[0,t]$ follows a Poisson$(\lambda t)$ distribution, then we have that the sequence of inter-arrival times are independent and identically distributed Exponential$(\lambda)$ random variables. Hence, the conditional distribution we are attempting to find is equivalent to finding the conditional distribution of the (unit normalized) arrival times of the first $n$ arrivals, given that we know the arrival time of the $(n+1)th$ arrival.\\
\noindent
Hence, if we take $0 < t_1 < \cdots < t_n < 1$, it follows that the conditional probability that there is one arrival in each interval of the form $(t_i,t_i+dt_i)$ and no arrivals outside of the union of these intervals $(1-\sum_{i=1}^n dt_i)$, given that there are definitely $n$ arrivals in the (0,1) interval is approximately:
$$f \biggl(\frac{S_1}{S_{n+1}},\cdots,\frac{S_n}{S_{n+1}} \biggr| S_{n+1} \biggr)
\approx \frac{e^{-(1-\sum_{i=1}^n dt_i)} \prod_{i=1}^n \frac{e^{-dt_i} dt_i}{1!}} {\frac{e^{-1}1^n}{n!}}
= \frac{n! e^{-(1-\sum_{i=1}^n dt_i)}e^{-\sum_{i=1}^n dt_i} dt_1\cdots dt_n}{e^{-1}}$$
$$= n! dt_1\cdots dt_n.
\hspace{5 pt} \square$$
\begin{center}
\line(1,0){450}
\end{center}
% PROBLEM 2
%PART A
\noindent
(2) (a) Since we just showed that $X_{(k)}$ is equivalent in distribution to $\frac{S_k}{S_{n+1}}$, it follows that if $\frac{S_k}{S_{n+1}} \overset{p}\to \alpha$ then $X_{(k)}\overset{p}\to \alpha$ as well. $\surd$\\
\noindent
Now, using the Weak Law of Large Numbers and the definition of $\alpha$, we find:
$$\frac{S_k}{S_{n+1}}
= \frac{\sum_{i=1}^k Y_i}{\sum_{i=1}^n Y_i}
= \frac{\frac{1}{n}\sum_{i=1}^k Y_i}{\frac{1}{n}\sum_{i=1}^n Y_i}
= \frac{\frac{\alpha}{k}\sum_{i=1}^k Y_i}{\frac{1}{n}\sum_{i=1}^n Y_i}
= \alpha \frac{\frac{1}{k}\sum_{i=1}^k Y_i}{\frac{1}{n}\sum_{i=1}^n Y_i}
\overset{p}\to \alpha \frac{\ex Y_1}{\ex Y_1}
= \alpha.
\hspace{5 pt} \square$$
%PART B
\noindent
(b)
$$\prob(\sqrt{n}(X_{(k)}-\alpha) \leq t)
= \prob(X_{(k)} \leq \frac{t}{\sqrt {n}}+\alpha)
= \prob(\sum_{i=1}^n \ind(X_i \leq \frac{t}{\sqrt {n}}+\alpha) \geq k)$$
$$= \prob \biggl(\frac{1}{n} \sum_{i=1}^n \ind (X_i \leq \frac{t}{\sqrt {n}}+\alpha) \geq \alpha \biggr)$$
$$= \prob \biggl\{ \sqrt{n} \biggl(\hat{F}_n \biggl(\frac{t}{\sqrt {n}}+\alpha \biggr)-F \biggl(\frac{t}{\sqrt {n}}+\alpha \biggr) \biggr)
\geq \sqrt{n} \biggl(\alpha-F\biggl(\frac{t}{\sqrt {n}}+\alpha \biggr) \biggr) \biggr\}$$
$$\approx 1-\Phi \biggl(\frac{\sqrt{n}(\alpha-F(\frac{t}{\sqrt {n}}+\alpha))}{\sqrt{F(\frac{t}{\sqrt {n}}+\alpha)(1-F(\frac{t}{\sqrt {n}}+\alpha))}}\biggr)$$
Now we know that $F(\frac{t}{\sqrt {n}}+\alpha)
\to F(\alpha)$ so that $\sqrt{n}(F(\frac{t}{\sqrt {n}}+\alpha)-\alpha) \to f(\alpha)$. Consequently:
$$\prob(\sqrt{n}(X_{(k)}-\alpha) \leq t)
\to 1-\Phi \biggl( \frac{-f(\alpha)t}{\sqrt{F(\alpha)(1-F(\alpha))}} \biggr)$$
Hence, we find:
$$\sqrt{n}(X_{(k)}-\alpha)
\overset{d}\to N \biggl(0,\frac{\alpha(1-\alpha)}{f^2(\alpha)} \biggr)
= N \biggl(0,\frac{F(\alpha)(1-F(\alpha))}{f^2(\alpha)} \biggr)
= N (0,\alpha(1-\alpha)). \hspace{5 pt} \square$$
%PART C
\noindent
(c) As for the median, it is apparent that in the framework of (b), here we have $k=\frac{n}{2}$ so that $\alpha = \frac{1}{2}$. Thus:
$$\sqrt{n}(X_{(\frac{n}{2})}-\frac{1}{2})
\overset{d}\to N(0,\frac{1}{4}). \hspace{5 pt} \square$$
\begin{center}
\line(1,0){450}
\end{center}
% PROBLEM 3
%PART A
\noindent
(3) (a) We can utilize the cdf $F(x) = \int_{-\infty}^x f(x)dx$ to create a bijective mapping between $[0,1]$ and $\mathbb{R}$. Thus, if $X_i \overset{iid}\sim f$ then $U_i = F(X_i) \overset{iid}\sim U[0,1]$. Additionally, if we assume that $f(x)$ has no discontinuities, then it follows from the definition of $F$ that $F(x)$ is continuous in F. Consequently, from the Continuous Mapping Theorem we have that if we let $\alpha = \frac{k}{n}$, then:
$$ X_{(k)}
= F^{-1}( F(X_{(k)}))
= F^{-1}(U_{(k)})
\overset{p}\to F^{-1}(\alpha).
\hspace{5 pt} \square$$
%PART B
\noindent
(b) In the derivation of 2(b), we did not assume that $X$ was from a uniform distribution, until the very last step. Hence, we can apply the results to that problem here:
$$\sqrt{n}(X_{(k)}-F^{-1}(\alpha))
\overset{d}\to N \biggl(0,\frac{F(F^{-1}(\alpha))(1-F(F^{-1}(\alpha)))}{f^2(F^{-1}(\alpha))} \biggr)
= N \biggl(0,\frac{\alpha(1-\alpha)}{f^2(F^{-1}(\alpha))} \biggr). \hspace{5 pt} \square$$
%PART C
\noindent
(c) Similar to problem 2, the median is just a special case of part (b) with $\alpha = \frac{1}{2}$. Thus, if $m$ is the value such that $\int_{-\infty}^m f(x) dx = \frac{1}{2}$, then it follows that:
$$\sqrt{n}(X_{(\frac{n}{2})}-m)
= \sqrt{n}(X_{(\frac{n}{2})}-F^{-1}(\frac{1}{2}))
\overset{d}\to N \biggl(0,\frac{\frac{1}{2}(1-\frac{1}{2})}{f^2(F^{-1}(\frac{1}{2}))} \biggr)
= N \biggl(0,\frac{1}{4f^2(m)} \biggr). \hspace{5 pt} \square$$
\begin{center}
\line(1,0){450}
\end{center}
% PROBLEM 4 <-- Did Not Attempt
% PROBLEM 5
%PART A
\noindent
(5) (a) First note that:
$$F_{T_n} (t)
= \prod_{i=1}^n F_{X_i} (t)
= F_X(t)^n
= (1-e^{-t})^n.$$
Hence, it follows that:
$$\prob(T_n - \log n \leq t)
= \prob(T_n \leq t+\log n)
= (1-e^{-(t+\log n)})^n
= \biggl(1-\frac{e^{-t}}{n} \biggr)^n
\to e^{-e^{-t}}.$$
Thus, $(T_n-\log n) \overset{d}\to Y$ where $F_Y = e^{-e^{-t}}.$ $\square$\\
%PART B
\noindent
(b) First note that:
$$F_{T_n}(t)
= \prod_{i=1}^n F_{X_i}(t)
= F_X(t)^n
= (1-t^{-\alpha})^n.$$
Hence, it follows that:
$$\prob(n^{-1/\alpha}T_n \leq t)
= \prob(T_n \leq t n^{1/\alpha})
= (1-(tn^{1/\alpha})^{-\alpha})^n
= \biggl(1-\frac{t^{-\alpha}}{n} \biggr)^n
\to e^{-t^{-\alpha}}.$$
Thus, $n^{-1/\alpha}T_n \overset{d}\to Y$ where $F_Y = e^{-t^{-\alpha}}.$ $\square$
\begin{center}
\line(1,0){450}
\end{center}
% PROBLEM 6
\noindent
(6) We have from (a) that:
$$G_n(\theta_0)+o_p(1) \overset{p}\to G(\theta) + 0 = G(\theta).$$
Additionally, from $(a)$ it follows that there exists a $\theta^*$ such that:
$$\prob(|G_n(\hat{\theta}_n)-G(\theta^*)|>\varepsilon) \to 0$$
Consequently, from the given constraint on $G_n(\hat{\theta}_n)$ it follows that:
$$G_n(\hat{\theta}_n) \overset{p}\to G(\theta^*) \geq G(\theta)$$
Now, condition (b) implies that $G(\theta_0)$ is the unique maximizer of $G(\theta)$ across all $\theta \in \Theta$. Thus:
$$\theta^* = \theta \Rightarrow \hat{\theta}_n \overset{p}\to \theta_0. \hspace{5 pt} \square$$
\begin{center}
\line(1,0){450}
\end{center}
\end{document}